Betatron x-ray radiation in the self-modulated laser wakefield acceleration regime: prospects for a novel probe at large scale laser facilities. (18th December 2018) - Albert, F.; Lemos, N.; Shaw, J.L.; King, P.M.; Pollock, B.B.; Goyon, C.; Schumaker, W.; Saunders, A.M.; Marsh, K.A.; Pak, A.; Ralph, J.E.; Martins, J.L.; et al.
Abstract: This paper presents an experimental and theoretical study of betatron x-ray radiation from laser wakefield acceleration in the self-modulated regime. Our experiments use picosecond duration laser pulses up to 150 J, for plasmas with electronic densities on the order of 10 19 cm −3 . In the self-modulated regime, electrons accelerated in the wake of the laser pulse are subject to both the longitudinal plasma and transverse laser electrical fields. As a result, they undergo oscillations and radiate a synchrotron-like spectrum. In our experimental configuration, electrons accelerated up to about 300 MeV, as well as betatron x-ray spectra with energies of 10 s of keV and photon fluxes between 10 8 –10 10 photons/eV/Sr are reported. Our experiments open the prospect of using betatron x-ray radiation for applications, and the source could be competitive with current x-ray backlighting methods on multi-kilojoule laser systems used for high energy density or fusion sciences.